A disposable sampling device to collect volume-measured DBS directly from a fingerprick onto DBS paper. (September 2015) - Lenk, Gabriel; Sandkvist, Sören; Pohanka, Anton; Stemme, Göran; Beck, Olof; Roxhed, Niclas
Background: DBS samples collected from a fingerprick typically vary in volume and homogeneity and hence make an accurate quantitative analysis of DBS samples difficult.Results: We report a prototype which first defines a precise liquid volume and subsequently stores it to a conventional DBS matrix. Liquid volumes of 2.2 µl ± 7.1% (n = 21) for deionized water and 6.1 µl ± 8.8% (n = 15) for whole blood have been successfully metered and stored in DBS paper.Conclusion: The new method of collecting a defined volume of blood by DBS sampling has the potential to reduce assay bias for the quantitative evaluation of DBS samples while maintaining the simplicity of conventional DBS sampling.